2020
DOI: 10.21203/rs.3.rs-17855/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers to Childhood Immunization in Sub-Saharan Africa: A Systematic Review

Abstract: Background Immunization to prevent infectious diseases is a core strategy to improve childhood health as well as survival. It remains a challenge for some African countries to attain the required childhood immunization coverage. We aim at identifying individual barriers confronting parents/caretakers, providers, and health systems that hinder childhood immunization coverage in Sub-Saharan Africa.Method This systematic review searched PubMed/MEDLINE, Web of Science and EMBASE. We restricted to published article… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…Despite the adult population involved in this study, a surprising 28.7% of the study participants indicated that their decision to take the Covid-19 vaccines is dependent upon the guidance of their parents. This strong influence of parents on vaccine uptake by their wards have been supported by findings from several other studies at different parts of the world (27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 65%
“…Despite the adult population involved in this study, a surprising 28.7% of the study participants indicated that their decision to take the Covid-19 vaccines is dependent upon the guidance of their parents. This strong influence of parents on vaccine uptake by their wards have been supported by findings from several other studies at different parts of the world (27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 65%